Plan de gestión integral de residuos solidos hospitalarios y similares en el E.S.E. Centro de Salud de Cucunubá Cundinamarca (2020)
At the E.S.E Centro de Salud del municipio de Cucunubá located in Cundinamarca, the degree project was carried out, which consisted of designing the Comprehensive Management Plan for Waste Management, based on environmental and biosafety fundamentals that must be had in all entities that provide health services, taking into account that this health center did not have a Comprehensive Management Plan for the Management of Hospital Waste from the beginning of its services. To carry out our Comprehensive Management Plan for the Management of Hospital Waste, the diagnosis that has been developed within the health center was taken as a basis, where the organization of the institution is taken into account and the management that has been given to solid waste An identification of the processes where deficiencies are seen in the management of solid waste were carried out carrying out improvement plans within the health center, in addition to this, proposals and recommendations are generated to comply with that is stipulated within the comprehensive management plan. The methodology used for this study has an analytical method due to the fact that a literature review is carried out for the development of the PGIRS in the health center, with a qualitative approach that allows us to obtain its documentation and make the respective visits, which They gave us observation and interview techniques to collect information through instruments such as the field diary and electronic devices. Taking into account the diagnosis, the processes and the stages, the health center is recommended to continue with the plans and programs that were developed in the PGIRS based on decrees 2676 of 2000 and 1164 of 2002. The PGIRS will help the health center to prevent, correct and monitor an inadequate management of solid hospital waste, preventing impacts on human health and the environment.